Thermal stability of ε-Ga2O3 polymorph. (November 2017) - Fornari, R.; Pavesi, M.; Montedoro, V.; Klimm, D.; Mezzadri, F.; Cora, I.; Pécz, B.; Boschi, F.; Parisini, A.; Baraldi, A.; Ferrari, C.; Gombia, E.; et al.
Abstract: The thermal stability of ε-Ga2 O3 polymorph was studied by complementary methods. Epitaxial films of ε-Ga2 O3 grown on c-oriented sapphire were annealed at temperatures in the range 700–1000 °C and then investigated by X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM). In addition, Differential Scanning Calorimetry (DSC) up to 1100 °C was carried out on fragments of pure ε-Ga2 O3 taken from a very thick layer. The results clearly indicate that ε-Ga2 O3 initiates modifying its crystallographic structure above 650 °C, as demonstrated by a mild endothermic bent of the DSC curves. However, the effective transition to β-phase occurs quite suddenly at 880–920 °C, depending of the DSC heating rate. XRD and TEM results confirm this evidence. TEM investigation in particular shows that after annealing at 1000 °C and rapid cooling the film is completely made of β-Ga2 O3 grains, most of them with orientation (310) respect to the sapphire substrate. However, if the cooling rate is substantially reduced, the converted β-Ga2 O3 layer assumes the standard orientation (−201) parallel to (00.1) of the Al2 O3 substrate. Based on the results of this study we conclude that ε-Ga2 O3 may conveniently be used for device fabrication, exploiting its higher crystallographic symmetry and better matching to sapphire. However, all fabrication steps must be carried out at temperatures below 700 °C. Graphical abstract: Image